Medical disputes and mediation in China: Government and responsibility shifting. (November 2019) - Zhang, Jing; Cai, Yongshun
Because of the heavy burden that the resolution of social conflicts imposes on the Chinese government, the government is motivated to delegate or shift its conflict resolution responsibilities to specialized institutions, including social organizations. However, the effectiveness of responsibility shifting is conditional on the types of conflict and social contexts. Focusing on the resolution of medical disputes in China, this article examines the conditions under which the government can avoid direct and heavy involvement in dispute resolution. The government can effectively delegate the responsibility for resolving conflicts when the disputing parties perceive the mediation agencies as impartial. Having effective institutions thus limits government intervention to only a small number of disputes. This study is based on an analysis of 1351 medical disputes and about 80 interviews with parties involved in dispute resolution.